Book Review: Vulnerable Futures, Transformative Pasts: On Vulnerability, Temporality, and Ethics by Miri Rozmarin, Peter Lang, 2017, 194 pages. ISBN 978-1-78707-392-0 (ePub) (also available in print, ePDF and mobi) - Geerts, Evelien (Redescriptions : yearbook of political thought, conceptual history and feminist theory, 2020)
Published in 2017 and originally planned in as a 2020 summer break read, feminist philosopher Miri Rozmarin’s second book, Vulnerable Futures, Transformative Pasts: On Vulnerability, Temporality, and Ethics, turned into an even more timely, provocative reading experience than initially expected because of the global eruption of the now so familiar-feeling COVID-19 crisis. [...]vulnerability is contradicted to the basic conditions for a person’s agency, and thus associated with the lessening of personhood. [...]an approach does not instantaneously label vulnerability as the negative mirror image of agency (and vice versa), but, based upon Levinasian theory, regards the phenomenon as a ‘sensitivity’ (50) that is typical for human intersubjective relations. Butler’s approach has mostly been spotlighted in Precarious Life ([2004] 2006)her post-9/11 book that articulates an ethics of non-violenceand later works (see e.g. Butler 2009; 2016) in which the distinction between ontological precariousness and precarity, or the specific socio-economic and political conditions that have rendered certain subjects more vulnerable to injustice, poverty, and the like is made more intelligible.